2005
DOI: 10.1161/01.hyp.0000184225.05629.51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endurance Training on Blood Pressure, Blood Pressure–Regulating Mechanisms, and Cardiovascular Risk Factors

Abstract: Abstract-Previous meta-analyses of randomized controlled trials on the effects of chronic dynamic aerobic endurance training on blood pressure reported on resting blood pressure only. Our aim was to perform a comprehensive meta-analysis including resting and ambulatory blood pressure, blood pressure-regulating mechanisms, and concomitant cardiovascular risk factors. Inclusion criteria of studies were: random allocation to intervention and control; endurance training as the sole intervention; inclusion of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
539
12
66

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 758 publications
(666 citation statements)
references
References 90 publications
49
539
12
66
Order By: Relevance
“…The reduction of resting BP was more pronounced in the hypertensive study groups (À6.9/À4.9 mm Hg) than in others (À1.9/À1.6 mm Hg). 3 Compared with these data, our results reveal even higher reductions of BP, indicating an efficient training concept. As reflected by the increase of FMD, the decrease of BP is associated with an improvement of endothelial function.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The reduction of resting BP was more pronounced in the hypertensive study groups (À6.9/À4.9 mm Hg) than in others (À1.9/À1.6 mm Hg). 3 Compared with these data, our results reveal even higher reductions of BP, indicating an efficient training concept. As reflected by the increase of FMD, the decrease of BP is associated with an improvement of endothelial function.…”
Section: Discussionmentioning
confidence: 58%
“…1,2 Whereas cardiovascular training can induce systolic and diastolic blood pressure reductions of approximately 3-4 mm Hg in normotensives, this phenomenon is even more pronounced in hypertensives. 3 Shear stress -as induced by physical exercise -is a potent stimulus on endothelial cells for an increase in nitrous oxide (NO)-production leading to improved endothelial function and reduced vascular resistance. 4 The extent of cardiovascular benefits, however, depends strictly on the concept of the endurance programme.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of physical activity interventions that do not significantly alter body weight have documented 5% to 35% reductions in TG levels (52,53) and/or 3% to 5% increases in HDL values (32,52). Lastly, the blood pressure reductions induced through chronic exercise do not appear to be related to alterations in body weight or abdominal obesity (54). In fact, a large meta-analysis (54), which reported an overall beneficial effect of chronic exercise on blood pressure, found that the average weight loss across the reviewed trials was largely inconsequential (-1.2 kg).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 99%
“…13 Regular physical exercise reduces AP, 14,15 adjusts body composition, 16,17 increases aerobic capacity, 15,16 controls serum fat levels 16 and improves cardiac autonomic control. 18 The benefits of aerobic physical training on cardiac autonomic control have been well documented in experimental and clinical studies.…”
Section: Introductionmentioning
confidence: 99%